Training Ludwig declarative deep learning models using Mac Studio M1Ultra. (Pragmatic AI Solutions, 2022)
Learn to use the M1Ultra to train a deep learning model using Ludwig the declarative deep learning framework. 00:00 Intro 00:31 Checking out M1Ultra 64 Core GPU and 20 Core CPU 01:31 Launching Visual Studio Code with a virtualenv 01:49 Checking out Makefile for Ludwig install process on Mac M1Ultra 64 Core GPU and 20 Core CPU machine 03:27 Training the Ludwig model using PyTorch Deep Learning in 30 seconds. Rotten Tomatoes binary classification. 04:28 Checkout out model structure on disk.